2020
DOI: 10.3390/en13143587
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalysis in (Bio)Ethanol Conversion to Chemicals and Fuels: Thermodynamics, Catalysis, Reaction Paths, Mechanisms and Product Selectivities

Abstract: In gas/solid conditions, different chemicals, such as diethylether, ethylene, butadiene, higher hydrocarbons, acetaldehyde, acetone and hydrogen, can be produced from ethanol with heterogeneous catalytic processes. The focus of this paper is the interplay of different reaction paths, which depend on thermodynamic factors as well as on kinetic factors, thus mainly from catalyst functionalities and reaction temperatures. Strategies for selectivity improvements in heterogeneously catalyzed processes converting (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…It needs to be noted that hard template synthesis was investigated as a novel procedure for the synthesis of lanthanum oxide‐based material in the work presented here, and to our knowledge it has not been previously reported in the open literature. The La‐based hydroxide prepared using these two methods was compared in terms of acid–base properties, sample morphology and catalytic performances in (bio)ethanol conversion, which can be efficiently used as a probe reaction for the surface characterization of an oxide 38 . In fact, over a Lewis acid, ethyl ether and ethylene are produced, while over Brønsted acid sites, together with the above‐cited products also high olefins and aromatics can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be noted that hard template synthesis was investigated as a novel procedure for the synthesis of lanthanum oxide‐based material in the work presented here, and to our knowledge it has not been previously reported in the open literature. The La‐based hydroxide prepared using these two methods was compared in terms of acid–base properties, sample morphology and catalytic performances in (bio)ethanol conversion, which can be efficiently used as a probe reaction for the surface characterization of an oxide 38 . In fact, over a Lewis acid, ethyl ether and ethylene are produced, while over Brønsted acid sites, together with the above‐cited products also high olefins and aromatics can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol starts to convert only at T>600 K. The production of ethylene starts together and is always far higher than that of ethyl ether, the reverse of what happens on most acid catalysts at low conversion. 42 Almost simultaneously to the dehydration reactions, the production of acetaldehyde is also observed, followed very rapidly by combustion to CO 2 , that becomes the most abundant product at 773 K. Ethanol conversion is limited to ~70% achieved at the highest temperature. The poor activity of amorphous silica in ethanol dehydration has been previously reported by our group 43 and is associated to its poor acidity.…”
Section: Catalytic Activity In Ethanol Conversion In the Presence Of Oxygen -Tpsr Studiesmentioning
confidence: 99%
“…22,23 In the experimentally determined thermodynamic equilibrium between EtOH, diethyl ether (DEE) and ethene at atmospheric pressure the ratio of DEE : ethene is 1 : 1 at roughly 370 K, while above 450 K no significant amount of DEE is observed. 24 However, in many experimental studies the actually observed product ratio greatly varies with the overall reaction conditions, 25 such as EtOH pressure, 26 catalyst contact time, overall conversion and temperature. A particularly high sensitivity of the ethene selectivity to the catalyst contact time and temperature has been found in H-SAPO-34 in the narrow temperature interval from 458 K to 503 K. 27 Many other experimental works have been reported.…”
Section: Introductionmentioning
confidence: 99%